DECISION SUPPORT SYSTEM FOR DETERMINING QUALITY BANANA CHIPS USING THE WEIGHTED PRODUCT METHOD - Siti Lamunah; Kasmi Kasmi; Keny Puspita Sari; Sucipto Sucipto (IJISCS (International Journal of Information System and Computer Science), 2018)
Decision support system is part of computer-based information commonly used to support decision making in an organization or decision support system can be generated using several methods, one of which is the weighted product (WP) method. This method is chosen because of its completion method by using multiplication to associate attribute values, where the value must be raised first with the attribute weights in question. There are four types of  banana samples that can be used for making banana chips, namely kepok banana, ambon banana, jackfruit banana, horn banana. Of four bananas are selected kepok banana and horns banana are good to be made with chips with an alternative value 0.270118051.